Two-Frequency Pulsed Laser Irradiation to Stimulate the Development of Coniferous Trees - Lobanov, A. V.; Apasheva, L. M.; Smurova, L. A.; Ovcharenko, E. N.; Budnik, M. I.; Savransky, V. V. (Russian journal of physical chemistry. B, 2024)
The possibility of using radiation from a two-frequency pulsed copper vapor laser with wavelengths of 510.6 and 578.2 nm with an exposure of 30 to 120 s to stimulate the development of coniferous trees (spruce, pine, larch) with single seed irradiation is shown. The stimulation effect manifests itself at various early stages of development, such as the awakening of seeds in the aquatic environment in the first hours of the experiment (according to the electron absorption spectroscopy data), seed germination, and seedling growth under stressful cultivation conditions. Possible causes of light exposure to plant seeds are discussed.